FACILLITIES DEGRADATION OF FLUID POLLUTION SUBSTANCES FROM COMPOSITE MATERIALS BY UTILIZATION OF WASTES - RUZINSKA, Eva (Trends in education, 2009)
The paper deals with the problem of decreasing air pollution by hazardous chemical (vapour) substances are released from various materials which furnished building interiors. Together are presented experimental results obtained from preparation of perspective wooden composites with reduced released formaldehyde content.
Keywords: fluid pollution substances; formaldehyde; wooden composite materials.